The Rank of Socioeconomic Status within a Class and the Incidence of School Bullying and School Absence - Atsushi Inoue; Ryuichi Tanaka (Institute of Labor Economics (IZA), 2024)
In this study, we examine the impact of a student's household socioeconomic status (SES) rank within a class on two critical factors affecting the accumulation of human capital: school bullying victimization and school absence. We identify the effect from the variation of a within-class SES rank of students assigned to different schools and classes, controlling the absolute level of SES and class fixed effects. Using the data from middle-school students in the Trends in International Mathematics and Science Study (TIMSS), we find that, although the absolute level of SES is negatively associated with these incidences, students with a high SES rank within a class are more likely to be the victims of school bullying and to be absent from school. We confirm that these results are robust when the sample is restricted to schools where students' assignment to classes is as good as random.
Keywords: I21; 330; rank; socioeconomic status; school bullying; school absence